BUDAYA DAN SENI KREATIF TARI KECAK DI BALI - Adinda Putri Dewi, Rahelia; Aulia Septya Kusuma Wardani, Lintang (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2023)
Kecak Dance is a traditional art form originating from Bali, Indonesia, which combines dance and theater aspects. The art was introduced in the 1930s by Wayan Limbak and German artist Walter Spies, who were inspired by the Sanghyang ceremony which has spiritual significance in Balinese society. The Kecak Dance depicts the epic story of Ramayana, especially about the fight between Rama and Ravana to save Goddess Sinta, which symbolizes the eternal war between good and evil.